American Chinese Medical Exchange Society 2010 Annual Conference - ACMES, ACMES (North American Journal of Medicine and Science, 2010)
On October 30, 2010, American Chinese Medical Exchange Society (ACMES) held her annual conference at the Best Western Hotel near Harvard Medical School featuring “Asian Health Education”, participated by nearly 300 physicians and health care professionals across the country, including visiting physicians and scholars from China.